A IMPROVING COMPREHENSIVE ACADEMIC WRITING SKILL: IMPROVING COMPREHENSIVE ACADEMIC WRITING SKILL - Rustamov, Abdushukur (Журнал иностранных языков и лингвистики, 2022)
Writing is one of the main and inseparable pieces of any language. People learn, read information in the writings. The importance of writing skill is dated back to the ancient history of human being.